Effects of O‐methylated (−)‐epigallocatechin gallate (EGCG) on LPS‐induced osteoclastogenesis, bone resorption, and alveolar bone loss in mice. Issue 12 (15th November 2017) - Tominari, Tsukasa; Ichimaru, Ryota; Yoshinouchi, Shosei; Matsumoto, Chiho; Watanabe, Kenta; Hirata, Michiko; Grundler, Florian M.W.; Inada, Masaki; Miyaura, Chisato
Abstract : (−)‐Epigallocatechin‐3‐ O ‐gallate (EGCG), present in green tea, exhibits antioxidant and antiallergy effects. EGCG3″Me, a 3‐ O ‐methylated derivative of EGCG, has been reported to show similar biological functions; the inhibitory activity of EGCG3″Me in a mouse allergy model was more potent than that of EGCG, probably due to the efficiency of absorption from the intestine. However, the functional potency of these EGCGs is controversial in each disease model. We previously observed that EGCG suppressed inflammatory bone resorption and prevented alveolar bone loss in a mouse model of periodontosis. In this study, we examined the role of EGCG3″Me in bone resorption using a mouse model of periodontitis. Lipopolysaccharide (LPS)‐induced osteoclast formation was suppressed by adding EGCG3″Me to cocultures of osteoblasts and bone marrow cells, and LPS‐induced bone resorption was also inhibited by EGCG3″Me in calvarial organ cultures. EGCG3″Me acted on osteoblasts and suppressed prostaglandin E (PGE) production, which is critical for inflammatory bone resorption, by inhibiting the expression of COX‐2 and mPGES‐1, key enzymes for PGE synthesis. In osteoclast precursor macrophages, EGCG3″Me suppressed RANKL‐dependent differentiation into mature osteoclasts. In a mouse model of periodontitis, LPS‐induced bone resorption was suppressed by EGCG3″Me in organ culture of mouse alveolar bone, and the alveolar bone loss was further attenuated by the treatment of EGCG3″Me in the lower gingiva in vivo . EGCG3″Me may be a potential natural compound for the protection of inflammatory bone loss in periodontitis. Abstract : Periodontitis is an inflammatory bone disease caused by infection, the progression of which results in alveolar bone destruction and tooth loss. (−)‐Epigallocatechin‐3‐ O‐ gallate (EGCG) is a green tea‐derived catechin. We show here that EGCG3″Me, a methylated derivative of EGCG, suppressed inflammatory bone loss and prevented periodontitis in a mouse model, suggesting beneficial roles of green tea in oral health.